2018
DOI: 10.1002/clc.22902
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the contemporary management of HIV patients admitted for acute myocardial infarction

Abstract: AMI was more common in males than females with HIV. Females with HIV were more likely to be younger and black and less likely to be revascularized by PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…Ogunbayo et al evaluated sex differences in management of MI in PLWH in a large US‐based cohort [31]. Among those with an acute MI, WLWH were younger (53.1 vs. 54.3), more likely than MLWH to be black (57.2 vs. 36%), to have diabetes (38.5% vs. 24.1%), to be obese (14.1% vs. 5.2%) and to be anaemic (26.7% vs. 16.9%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ogunbayo et al evaluated sex differences in management of MI in PLWH in a large US‐based cohort [31]. Among those with an acute MI, WLWH were younger (53.1 vs. 54.3), more likely than MLWH to be black (57.2 vs. 36%), to have diabetes (38.5% vs. 24.1%), to be obese (14.1% vs. 5.2%) and to be anaemic (26.7% vs. 16.9%).…”
Section: Resultsmentioning
confidence: 99%
“…Abraham et al [32] noted that the rate of HIV viral suppression was markedly lower in black than in non‐black participants (47% vs. 73%). Ogunbayo et al [31] also found that WLWH, of whom a higher proportion were black compared with the MLWH, were significantly less likely to undergo coronary revascularization following MI. These two studies, both from North America, highlight the need to explore sex and race‐related inequality in the healthcare setting as a barrier to WLWH accessing care.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have reported that women living with HIV have a significantly higher risk of CVD compared to seronegative females, and are less likely to be re-vascularized by PCI [ 23 , 24 , 25 ]. However, in this study, we found a high prevalence of women with HIV that underwent CC (41.2%) and PCI (36.4%).…”
Section: Discussionmentioning
confidence: 99%